Pengaruh penanaman modal asing (pma) dan penanaman modaldalam negeri (pmdn) terhadap pertumbuhan ekonomi serta kesejahteraan di kalimantan timur (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2020)
The purpose of this research is to find out,  The influence of foreign investment and domestic investment  on economic growth and welfare in East Kalimantan, in 2005 to 2019. This tape of research is quantitative. This study uses a path analysis tool with the SPSS21 Program. Based on the results of this study indicate that, foreign direct Investment has a negative and singnificant effect on Economic Growth, foreign direct Investment has a negative and not singnificant effect on Welfare in East Kalimantan. And direct Domestic Investment has a signifikan effect on Economic Growth, direct Domestic Investment has a not signifikan effect on Welfare in East Kalimantan. Indirectly Foreign Investment has negatif influence and Domestic Investment indirectly has a positive effect on Welfare in East Kalimantan. and Economic Growth has no significant effect on Welfare in East Kalimantan.